2023
DOI: 10.3389/fimmu.2023.1204831
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of mRNA-1273 and BNT162b2 COVID-19 vaccines in immunocompromised individuals: a systematic review and meta-analysis using the GRADE framework

Xuan Wang,
Katrin Haeussler,
Anne Spellman
et al.

Abstract: IntroductionDespite representing only 3% of the US population, immunocompromised (IC) individuals account for nearly half of the COVID-19 breakthrough hospitalizations. IC individuals generate a lower immune response after vaccination in general, and the US CDC recommended a third dose of either mRNA-1273 or BNT162b2 COVID-19 vaccines as part of their primary series. Influenza vaccine trials have shown that increasing dosage could improve effectiveness in IC populations. The objective of this systematic litera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 63 publications
(173 reference statements)
0
11
0
Order By: Relevance
“…The safety and efficacy of both mRNA-1273 and BNT162b2 in reducing the risk of SARS-CoV-2 infection in the general population and in adolescents have been demonstrated in numerous phase 3 clinical trials [14][15][16]. Subsequent observational studies have provided evidence of the protection offered by two doses of both mRNA vaccines against SARS-CoV-2 infection and against COVID-19 hospitalisation and hospital death [17][18][19][20][21][22], despite the emergence of variants [23][24][25], although several observational studies have demonstrated that the differences in formulation impact vaccine effectiveness [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The safety and efficacy of both mRNA-1273 and BNT162b2 in reducing the risk of SARS-CoV-2 infection in the general population and in adolescents have been demonstrated in numerous phase 3 clinical trials [14][15][16]. Subsequent observational studies have provided evidence of the protection offered by two doses of both mRNA vaccines against SARS-CoV-2 infection and against COVID-19 hospitalisation and hospital death [17][18][19][20][21][22], despite the emergence of variants [23][24][25], although several observational studies have demonstrated that the differences in formulation impact vaccine effectiveness [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Although both mRNA-1273 and BNT162b2 (Pfizer-BioNTech Comirnaty) COVID-19 vaccines and their subsequent variant-adapted vaccines are based on mRNA technology, the formulations of mRNA-1273 version, including their dosages and nanoparticle mRNA delivery systems, differ [11–14]. Studies have found VE differences between previous versions of the mRNA-1273 vaccine and the corresponding BNT162b2 vaccine in both the general [15–19] and IC populations [20], with mRNA-1273 formulations resulting in greater levels of protection. Wang et al, (2023) conducted a systematic literature review and meta-analysis based on 17 studies in the IC population [20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found VE differences between previous versions of the mRNA-1273 vaccine and the corresponding BNT162b2 vaccine in both the general [15–19] and IC populations [20], with mRNA-1273 formulations resulting in greater levels of protection. Wang et al, (2023) conducted a systematic literature review and meta-analysis based on 17 studies in the IC population [20]. The mRNA-1273 vaccine was found to be associated with a significantly lower risk of COVID-19 infection (relative risk [RR] for infection = 0.85 [95% CI 0.75-0.97]), hospitalizations (RR = 0.88 [95% CI 0.79-0.97]), and deaths (RR = 0.63 [95% CI 0.44-0.90]), compared to the BNT162b2 vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on previous versions of the mRNA vaccines have found higher VE values for different versions of the Moderna mRNA-1273 vaccine compared to the Pfizer-BioNTech BNT162b2 versions, including high-risk populations. [15][16][17][18][19][20][21] Given the new Fall 2023 vaccine campaign, with updated Fall 2023 vaccines from both Moderna and Pfizer-BioNTech it is important to determine the economic and clinical consequences of vaccination during the Fall 2023, and understand the impact of newly emerging variants, to assist in the decision-making process and inform currently ongoing NIP discussions. Additionally, as the Japanese government has previously recommended and funded a Spring season vaccination campaign for select high-risk populations, the economic and clinical consequences of continuing to fund this population needs to be explored, as it likely will be a discussion subject for the NIP in 2024.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the objective of this analysis is to estimate the economic and clinical impact of a NIP vaccination campaign from April 2024 onwards using the Fall 2023 updated mRNA COVID- 19 Moderna vaccine compared to the Fall 2023 updated mRNA COVID-19 Pfizer-BioNTech vaccine for adults 18 years of age and older, using a previously developed Susceptible-Exposed-Infected-Recovered (SEIR) model. 22 The impact of a Spring 2024 vaccination campaign in select, high-risk individuals (60-64 high-risk and 65+ general population; 65+ general population only) is also explored.…”
Section: Introductionmentioning
confidence: 99%